Treatment of striae distensae: An evidence-based approach. (2nd January 2019) - Forbat, Emily; Al-Niaimi, Firas
ABSTRACT: Striae distensae (SD), otherwise known as "stretchmarks, " are a common presenting complaint, particularly in young healthy women. SD are hypothesized to form in a patient when the cross-linked collagen is "overstretched" and rupture of this collagen matrix causes the striae. Thus, many treatments work by increasing collagen synthesis. This review critically appraises the evidence to date for the treatment of SD, including both energy-based devices and topical treatments.